Penerapan Permainan Edukatif ‘Harta Karun’ Berbasis Problem Based Learning terhadap Literasi Sains Siswa - Susilowati, Ayu Rizki; Saputra, Yuda Ardi (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to describe increasing scientific literacy through the 'Harta Karun' educational game based on problem-based learning. The method is classroom action research (CAR). The subjects were students of class VI A SD Negeri 1 Pandansurat totaling 21 students. The results showed there was an increase in learning outcomes of science content from pre-cycle to cycle I by 38%. Then, from cycle I to cycle II by 43%. The increase in students' scientific literacy was also seen from the analysis of the questionnaire which was compiled based on competencies according to the OECD which had increased from pre-cycle to cycle II. These are: (1) explain the phenomenon scientifically; (2) competence in designing and evaluating scientific investigations; (3) interpreting data and evidence scientifically. It can be concluded that the application of the problem-based learning-based educational game 'Harta Karun' can improve the scientific literacy of grade VI elementary school students.